2014
DOI: 10.1016/j.bbmt.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Cytotoxicity of Sorafenib with Busulfan and Nucleoside Analogs in Human FMS-like Tyrosine Kinase 3 Internal Tandem Duplications–Positive Acute Myeloid Leukemia Cells

Abstract: Clofarabine (Clo), fludarabine (Flu), and busulfan (Bu) are used in pre-transplant conditioning therapy for patients with myeloid leukemia. To further improve their efficacy in FLT3-ITD-positive AML, we investigated their synergism with sorafenib (Sor). Exposure of FLT3-ITD-positive MV-4-11 and MOLM 13 cells to [Bu+Clo+Flu+Sor] resulted in synergistic cytotoxicity; no such synergism was observed in the FLT3-wild type THP-1 and KBM3/Bu2506 cell lines. The drug synergism in MV-4-11 cells could be attributed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…There were no significant differences in the platelet counts and hemoglobin levels in the peripheral blood of patients in the four groups (P>0.05), suggesting that simultaneous mutation of DNMT3A and FLT3-ITD contributes to increased WBC and myeloid progenitor cells. It was previously demonstrated that FLT3-ITD mutation can activate a downstream kinase through the continuous activation of protein tyrosine kinase, thereby triggering signal transduction and further inducing the spontaneous and non-receptor-dependent proliferation of leukocytes (27). However, the role of DNMT3A in cell proliferation remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant differences in the platelet counts and hemoglobin levels in the peripheral blood of patients in the four groups (P>0.05), suggesting that simultaneous mutation of DNMT3A and FLT3-ITD contributes to increased WBC and myeloid progenitor cells. It was previously demonstrated that FLT3-ITD mutation can activate a downstream kinase through the continuous activation of protein tyrosine kinase, thereby triggering signal transduction and further inducing the spontaneous and non-receptor-dependent proliferation of leukocytes (27). However, the role of DNMT3A in cell proliferation remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, new target drugs were developed and evaluated in AML patients either alone or in combination with chemotherapy [28]. As an example, the addition of cladribine to regimens containing Ara-C and anthracyclines (idarubicine) allows not only a higher complete remission rate, including patients with unfavorable karyotype, but also has a more significant advantage in OS [29].…”
Section: Discussionmentioning
confidence: 99%
“…Advances in cancer genomics have revealed a spectrum of somatic mutations that give rise to human AML, drawing our attention to its molecular evolution and clonal architecture [26,27,28]. Therefore, new target drugs were developed and evaluated in AML patients either alone or in combination with chemotherapy [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since [Flu+Clo+Bu] activates the DDR in AML cells [20], we examined if [Flu+Clo+Bu+Rom] would have similar effects in neoplastic T-cells. Since the activation of DDR is an early event, we exposed PEER cells to drugs for 24 hrs and analyzed them by Western blotting.…”
Section: Resultsmentioning
confidence: 99%